Distinction: Islam and Islamic Fundamentalism - Djamiatul Islamiyah (Institut Islam Nahdlatul Ulama Temanggung, 2020)
Fundamentalism, although many associate it with Islam, in reality this concept is a global phenomenon. So that it can happen to every other religion and civilization. Then why is it associated with Islam? In fact, whenever there is violence that threatens the stability of security, the assumption is that the subject is the Islamic movement. This is because some people perceive Islam as a religion with Islamic fundamentalism as a political ideology. Huttington, for example, in his writing Clash civilization, is seen by Tibi as having ignored the crucial difference between Islam as a religion and fundamentalism as political Islam. It must be admitted that there are distortions in understanding the verses of the Al-Qur'an as well as the political orientation and violence which are the main characteristics of almost all movements known as Islamic fundamentalism, causing them to sometimes be trapped in violence. But making generalizations that violence or terrorism is always synonymous with Islamic fundamentalism is a simplistic and unwise conclusion. Violent fundamentalism can also occur in other religions such as the Serbian orthodox, and Hindu fundamentalism which wants to realize India as Hindustan. To avoid prolonged conflict, it is time to revive peace by improving the political, economic and social conditions that triggered the emergence of Islamic fundamentalism rather than taking violent action against them. The time to revive peace is not through jihad or military force as revenge.